Male and Female Characters’ Crying in Jane Austen’s “Sense and Sensibility” (1811) and Maria Wirtemberska’s “Malvina, or the Heart’s Intuition” (1816) - Ożarska, Magdalena (Respectus Philologicus, 2015)
Published in 1816, Malvina, or the Heart’s Intuition by Maria Wirtemberska appeared but five years after the publication of Jane Austen’s Sense and Sensibility (1811). My paper stipulates that Wirtemberska’s Malvina was to a large extent inspired by Austen’s novel although no straightforward evidence exists to suggest that the Polish writer was familiar with the works of the English author. Austen’s novels were not rendered into Polish in the nineteenth century: the first translation was published as late as 1934. But novels by Western European authors were read by educated Poles in their original language versions, or in French translations and adaptations. It is crucial to view Wirtemberska’s romance as a specimen of the same genre as Austen’s works because several parallels emerge in terms of the novel’s structure, motifs and characters. My paper looks at the ways in which the motif and images of crying are used in Austen’s and Wirtemberska’s novels. The two works seem a good choice for this kind of comparative analysis as they tackle various aspects of sensibility, a phenomenon which invoked mixed feelings among the novelists’ contemporaries, excitement and a sense of moral jeopardy included.